Potensi Ekstrak Temulawak (Curcuma xanthorrhiza Roxb) Terhadap Jamur Candida albicans Penyebab Keputihan - permata dewi, asiska (Yayasan Rahmatan Fiddunya Wal Akhirah, 2025)
Temulawak (Curcuma xanthorrhiza Roxb) is a plant of the Zingiberacea family. Temulawak is known as a traditional medicine in treating diseases such as antimicrobial, anticancer, digestive disorders and others. This study aims to determine the secondary metabolite compounds and antifungal activity of temulawak ethanol extract against Candida albicans fungus. The method used in the identification of secondary metabolite compounds is using color reagents and disc diffusion methods for antifungal activity tests. The results of the study showed that temulawak extract contains flavonoids and tannins. In the antifungal activity test with extract concentrations of 20%, 40%, 60% and 80%, the average diameter of the inhibition zone was 8.4 mm; 8.5 mm; 8.5 mm and 8.6 mm. In the positive control of nystatin, an inhibition zone of 31.4 mm was obtained and 6 mm in DMSO as a negative control. Based on the results of the study, the ethanol extract of temulawak has currently activity in inhibiting the growth of candida albicans.